Supplementary Figure 16 from Clinicopathologic, Genomic, and Immunophenotypic Landscape of ATM Mutations in Non–Small Cell Lung Cancer - Biagio Ricciuti (14951247) (2025)
Supplementary Figure 16. (A) Objective response rate, (B) progression-free survival, and (C) overall survival to PD-(L)1 inhibition monotherapy among patients with advanced/metastatic NSCLC, according to ATM/TP53 co-mutation status. (D) Objective response rate, (E) progression-free survival, and (F) overall survival to PD-(L)1 inhibition in combination with chemotherapy among patients with advanced NSCLC, according to ATM/TP53 co-mutation status.